2010
DOI: 10.1111/j.1744-6198.2010.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Nursing Telephone Counseling From Individuals Discharged in the Early Postoperative Period After Breast Surgery

Abstract: The study found that home follow-up of patients undergoing mastectomy was particularly important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Recommendations to improve patient care include redesigning the current assessment tool to include a psychosocial evaluation, revising the educational booklet to include information about potential feelings of social isolation following discharge from hospital and including strategies to cope with these emotions. A further recommendation was to present a business case to hospital management for the introduction of a telephone follow-up service (O'Brien et al, 1999;Sayin and Kanan, 2010). The final recommendation was to present the results of this study to the allied health team for their review and intervention.…”
Section: Discussionmentioning
confidence: 98%
“…Recommendations to improve patient care include redesigning the current assessment tool to include a psychosocial evaluation, revising the educational booklet to include information about potential feelings of social isolation following discharge from hospital and including strategies to cope with these emotions. A further recommendation was to present a business case to hospital management for the introduction of a telephone follow-up service (O'Brien et al, 1999;Sayin and Kanan, 2010). The final recommendation was to present the results of this study to the allied health team for their review and intervention.…”
Section: Discussionmentioning
confidence: 98%
“…15 Post-discharge clinician-initiated phone calls are an effective strategy for evaluating such concerns, enabling minor issues to be addressed via telephone counseling and providing a means to identify major issues that require escalation of the level of care. [15][16][17][18][19][20] These calls also have the potential to identify patients at high-risk for readmission. 15,16 However, such efforts are limited by the challenge of successfully reaching all patients via telephone, as prior data have shown that contact could not be made with up to 50% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, telephone consultation can reduce the anxiety of patients and take away any doubts in a limited amount of time, resulting in an increased intensity of the bond with professionals and the satisfaction of patients who receive care. "Telephone Consultation" was primarily designed for the follow-up of patients with chronic diseases, but a few studies report use of this intervention for surgical conditions such as urologic procedures, breast reconstruction, hip surgery, and heart surgery [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%